Czech Participation in Ukraine’s Reconstruction: Risks, Scenarios and Opportunities in the Housing Sector - Pavlák, Miroslav; Mentlík, Roman; Halouzka, Miroslav; Yurchenko, Svetlana (ACTA VŠFS)
Background: The post-conflict reconstruction of Ukraine, especially in the housing and construction sector, has become a strategic priority for the European Union and its member states. Despite declared support, the real participation of Central European businesses, including those from the Czech Republic, remains limited due to multiple legal, security and financial barriers. Aim: The paper aims to identify the conditions, instruments and risks influencing the potential engagement of Czech enterprises in the reconstruction of Ukraine's housing and construction sector after 2022, with emphasis on investment frameworks, scenario modelling, and institutional capacities. Methods: The study combines a qualitative case study (cooperation between the University of Finance and Administration and V. N. Karazin University in Kharkiv), stakeholder analysis based on coded interviews with Czech entrepreneurs, and quantitative investment scenario modelling (2024–2033). Data triangulation was applied to ensure internal validity. Results: Findings confirm that while institutional and financial instruments (e.g., Ukraine Facility) are in place, their uptake is limited by high perceived risk and a lack of implementation facilitators. Investment scenarios range from 65 to 95 billion USD depending on security and absorption conditions. Czech SMEs face specific constraints such as insufficient legal safeguards and capacity limits yet remain strategically positioned to benefit from targeted support schemes. Recommendations: Policy actors should prioritise the development of national coordination platforms, risk insurance schemes (e.g., via EGAP), and pilot cooperation models with Ukrainian institutions. Stronger links between academia, public sector and private firms are essential to de-risk market entry and build long-term resilience. Practical relevance/social implications: The research provides applicable insights for government agencies, export organisations and business associations aiming to support Czech firms in entering high-risk post-conflict markets. Moreover, it demonstrates the role of academic institutions as platforms for international capacity building and post-war recovery. Originality/value: This is the first study focusing on the Czech context of post-war investment in Ukraine, combining scenario modelling with a grounded case study. The integration of qualitative and quantitative methods provides a comprehensive Framework for further research and policy development.